FROM SACRED OFFERING TO WEARABLE ART: RECONTEXTUALIZING SAMPIAN IN CONTEMPORARY FASHION PRACTICE - Putra, I Gede Jaya; Wulansari, Vita (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2026)
Sampian is a ritual offering element integral to Hindu practices in Bali, carrying symbolic, philosophical, and aesthetic values beyond its devotional function. As contemporary society evolves, traditional objects such as sampian are increasingly explored beyond ritual contexts, entering the realms of art and fashion. This study examines the process of recontextualizing sampian from a sacred ritual object into wearable art within contemporary fashion, focusing on materiality, sustainability, and the transformation of meaning. Previous studies have addressed sampian primarily from the perspectives of ritual function, craft heritage, and traditional aesthetics; however, limited scholarly attention has been paid to its potential recontextualization within contemporary fashion discourse. This gap is significant given the intersection of cultural identity, ethical questions surrounding the use of sacred objects, and the growing discourse on sustainable fashion. Employing a qualitative, practice-based research approach, this study combines literature review, aesthetic and semiotic analysis—drawing on Bourriaud's Relational Aesthetics and Barthes' semiotic theory—and direct artistic production. Fieldwork and artwork creation were conducted in Bali between March and May 2022. The findings demonstrate that recontextualizing sampian produces distinct aesthetic forms combining woven janur, transparent textile, and bodily performance, while simultaneously expanding the object's cultural meaning rather than erasing it. The study argues that this transformation is ethically viable when grounded in cultural sensitivity, community engagement, and critical reflection, thus distinguishing responsible recontextualization from cultural appropriation.